2020
DOI: 10.2478/mmcks-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on consumer behavior in retail banking. Evidence from Romania

Abstract: The pandemic COVID-19 has severely affected the global economy. The strict lockdown measures have also changed the daily live, including consumer behavior in retail banking. In this context, the purpose of this paper is to investigate the impact of the COVID-19 crisis on consumer behavior in retail banking, with a special focus on the Romanian banking sector. To achieve our goal, we performed a survey among the Romanian consumers in retail banking, using as research method the field survey based on questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
1
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 23 publications
3
98
1
8
Order By: Relevance
“…In general, our study shows that COVID-19 has become a major driver of digital transformation in retail banks. This aligns with Baicu et al ( 2020 ), who found a strong increase in the consumption of mobile and Internet banking during the pandemic. As mentioned in introduction, Finnish banks can be seen as forerunners in digitalization and adjusting delivery channels, which prepared employees and customers in the Finnish banking sector for the change and helped them easily adapt to remote services.…”
Section: Discussionsupporting
confidence: 91%
“…In general, our study shows that COVID-19 has become a major driver of digital transformation in retail banks. This aligns with Baicu et al ( 2020 ), who found a strong increase in the consumption of mobile and Internet banking during the pandemic. As mentioned in introduction, Finnish banks can be seen as forerunners in digitalization and adjusting delivery channels, which prepared employees and customers in the Finnish banking sector for the change and helped them easily adapt to remote services.…”
Section: Discussionsupporting
confidence: 91%
“…Considering the prevalence of TPB and TAM, and their variants in consumer studies prior to COVID-19 (particularly regarding technologies) coupled with the massive popularity of technologies during the pandemic ( Baicu et al., 2020 : Sheth, 2020 ), the dominance of the two theories in this study is not surprising. Furthermore, they also explain the popularity of quantitative methods in the selected studies, and by specifying a set of directional relationships, they allow for testing the proposed models via structural equation modeling ( Kline, 2016 ).…”
Section: Descriptive and Bibliometric Analysismentioning
confidence: 82%
“…High importance is attached to COVID-19, the technological environment, and the politico-legal environment. Various studies indicate how the COVID-19 and available technology confluence has induced consumers to massively and rapidly adopt technologies and increase their consumption of highly digital business formats ( Baicu et al., 2020 : Sheth, 2020 ). Specifically, e-commerce and business platform formats solved possible shortage problems and allowed consumers to accumulate products ( Hao et al., 2020 ; Pillai et al., 2020 ).…”
Section: Systematization Of the Relevant Literaturementioning
confidence: 99%
“…When it comes to the protection of consumer rights within the EU, the European Commission and the governments of individual member states took very decisive actions. In the first stage of the crisis, numerous-often comparable-ad hoc measures were introduced in order to guarantee a higher level of security to people who lost their sources of income or those whose economic situation deteriorated (Baicu et al 2020).…”
Section: A Pan-european Perspective On the Solutions For The Financial Market In Response To The Crisis Triggered By The Covid-19 Pandemimentioning
confidence: 99%